Peran Kepala Sekolah Dalam Meningkatkan Mutu Pendidikan di Qismul Ali Al-Jam’iyatul Washliyah Medan (International Forum of Researchers and Lecturers, 2025)
This study aims to describe the role of the principal in improving the quality of education in Qismul Ali Al-Jam’Iyatul Washliyah. This study uses a qualitative approach with descriptive methods. Data sources were taken by purposive sampling and snowball sampling. Data collection was carried out through observation, interviews, and documentation studies. Data analysis was carried out using data reduction techniques, data presentation, and drawing conclusions. As for checking the validity of the data, namely by using triangulation of methods and sources. The results of the study indicate that there are 2 aspects of improvement carried out by the principal, namely: a) the role of the principal as a leader, namely by guiding and directing educators in creating interesting learning methods, then the principal tries to establish communication with his subordinates through greetings and listening directly to input from teachers and school employees regarding the problems they are facing, in decision making the principal applies a democratic and open system through deliberation and joint decisions, then the principal also becomes a good role model through diligent and disciplined behavior in working. To determine the program's achievement, the principal conducts regular supervision and evaluation of the learning process and learning materials, utilizing the results of this supervision to further improve learning activities through coaching and direction from the principal. b) The principal's role as a manager involves managing the school, starting with planning the school's work program at the beginning of the school year during work meetings involving teaching and administrative staff. The principal also involves teaching and administrative staff in various training activities to support competency. The principal also regularly maintains facilities and infrastructure. The findings of this study indicate that the principal has realized improvements in the quality of education at Qismul Ali Al-Jam'Iyatul Washliyah by implementing several improvement measures.